2015
DOI: 10.3389/fpsyg.2015.00966
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obesity and quality of life in Brazilian adults

Abstract: The incidence of obesity has reached epidemic proportions, affecting 30% of the adult population globally. During the last decade, the rising rates of obesity in developing countries has been particularly striking. One potential consequence of obesity is a decline in quality of life (QoL). Thus, the objective of the present study was to investigate the possible relationship between obesity, defined by body mass index (BMI), and QoL, evaluated using the short version of the World Health Organization Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 65 publications
(73 reference statements)
4
60
0
11
Order By: Relevance
“…High BMI in our study population was associated with higher pain and disability, lower functional capacity and lower QoL. These findings are comparable to a large body of evidence reporting negative consequences for QoL in individuals with higher BMI 383,384,[385][386][387] . The BMI of more than 65% of participants in the symptomatic group exceeded values for normal weight (>24.99 kg/m 2 ) 388 .…”
Section: Discussionsupporting
confidence: 84%
“…High BMI in our study population was associated with higher pain and disability, lower functional capacity and lower QoL. These findings are comparable to a large body of evidence reporting negative consequences for QoL in individuals with higher BMI 383,384,[385][386][387] . The BMI of more than 65% of participants in the symptomatic group exceeded values for normal weight (>24.99 kg/m 2 ) 388 .…”
Section: Discussionsupporting
confidence: 84%
“…The current results in congregant with [25] revealed significant decrease in quality of life among adolescent Saudi females with increased body mass. Similarly, [39] reported negative correlation between BMI and total score of quality of life among adult males and females in Brazil. Moreover, other studies were supported to the present study; the findings of [40] indicated negative association between body mass index, waist-hip ratio, body fat and health-related quality of life among Greek healthy adult males and females.…”
Section: Discussionmentioning
confidence: 99%
“…What is the prevalence of obesity in adult Saudi females? (2). How the adult Saudi females perceive their weight?…”
Section: Aim Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A obesidade, por sua vez, trata-se de um acúmulo de gordura corporal muito acima do índice de massa magra, a qual pode aumentar o risco de desenvolvimento de diversas patologias, tais como diabetes mellitus, hipertensão arterial, cardiopatias, dificuldades respiratórias, além de outras complicações. Pode ter origem genética, mas é causada principalmente por uma dieta excessivamente calórica associada a um baixo gasto de energia, criando assim reservas energéticas no tecido adiposo, as quais podem afetar a vida do indivíduo em âmbitos físicos, psicológicos, sociais e ambientais, influenciando diretamente em sua qualidade de vida 3 . A prevalência de sub e hipernutrição vêm sofrendo alterações em escala mundial, ao que muitos cientistas se referem por "transição nutricional".…”
Section: Introductionunclassified